Artificial Intelligence in Digital Health: Issues and Dimensions of Ethical Concerns - Ishengoma, Fredrick R. (2022)
Artificial intelligence (AI) is transforming the healthcare system at a breakneck pace by improving digital healthcare services, research, and performance, fueled by the combination of big data and strong machine learning algorithms. As a result, AI applications are being employed in digital healthcare domains of which some where previously regarded as only done by human expertise. However, despite AI's benefits in digital healthcare services, issues and ethical concerns need to be addressed. Using mapping review methodology, a taxonomy of issues and ethical concerns surrounding the employment of AI in healthcare is presented and discussed. Moreover, policy recommendations and future research directions are presented.